Heme acquisition in the parasitic filarial nematode Brugia malayi. Issue 10 (30th June 2016) - Luck, Ashley N.; Yuan, Xiaojing; Voronin, Denis; Slatko, Barton E.; Hamza, Iqbal; Foster, Jeremy M.
ABSTRACT: Nematodes lack a heme biosynthetic pathway and must acquire heme from exogenous sources. Given the indispensable role of heme, this auxotrophy may be exploited to develop drugs that interfere with heme uptake in parasites. Although multiple heme‐responsive genes (HRGs) have been characterized within the free‐living nematode Caenorhabditis elegans, we have undertaken the first study of heme transport in Brugia malayi, a causative agent of lymphatic filariasis. Through functional assays in yeast, as well as heme analog, RNAi, and transcriptomic experiments, we have shown that the heme transporter B. malayi HRG‐1 (BmHRG‐1) is indeed functional in B. malayi . In addition, Bm HRG‐1 localizes both to the endocytic compartments and cell membrane when expressed in yeast cells. Transcriptomic sequencing revealed that Bm HRG‐1, Bm HRG‐2, and Bm MRP‐5 (all orthologs of HRGs in C. elegans ) are down‐regulated in heme‐treated B. malayi, as compared tonon–heme‐treated control worms. Likely because of short gene lengths, multiple exons, other HRGs in B. malayi (BmHRG‐3–6) remain unidentified. Although the precise mechanisms of heme homeostasis in a nematode with the ability to acquire heme remains unknown, this study clearly demonstrates that the filarial nematode B. malayi is capable of transporting exogenous heme.—Luck, A. N., Yuan, X., Voronin, D., Slatko, B. E., Hamza, I., Foster, J. M. Heme acquisition in the parasitic filarial nematode Brugia malayi . FASEB J. 30, 3501–3514 (2016). www.fasebj.org